MODEL PENGUATAN KAPASITAS PEMERINTAH DESA SEBAGAIAGENDA UTAMA OPTIMASI PENGELOLAAN DESA MENUJUKEMANDIRIAN (Studi Kasus Desa Maipe Kecamatan Paju Epat Kabupaten Barito Timur) - Muhammad Noor; Muhammad Riyandi Firdaus; Farid Zaky Yopiannor (stiatabalong.ac.id, 2019)
This study aims (1) To map the problems of village government capacity in managing village governance, namely village development planning, village administration governance, village financial management, and village institutional strengthening. (2) Designing a new model to strengthen the capacity of village government as the main agenda for optimizing village management towards independence. The approach in this study uses a mixed method approach that prioritizes data mining through in-depth interviews, FGDs, Observation and Triangulation of data and relevant documents. This study also uses the PRA (participatory rural appraisal) approach which is assumed to be appropriate in order to solve research problems. Keywords: strengthening capacity; village government; village development The results of this study indicate that the condition of Maipem Village has a very strategic position in the mobilization pathway, natural resources that are quite potential, so that a significant effort is needed (political will) from the Government and stakeholders to develop a better Maipe Village. The description of the implementation of the Village Government is divided into four main research results, namely (1) the ability of the village government to carry out the functions of Village Administration Governance, data on Community Satisfaction with the Administrative Services Performance of Maipei Village illustrated that 43% of respondents said they were satisfied with administrative services, 20% respondents who said they were quite satisfied, as many as 17% of respondents said they were not satisfied, as many as 10% of respondents said they were very satisfied and as many as 10% of respondents said they were not satisfied. (2) The government's ability to carry out the functions of Village Development Planning has been consistent, namely carrying out the functions of development planning based on active community participation. (3) The ability of the village government to carry out the functions of village financial management still faces serious problems, namely the limited human resources both in quantity and in quality. (4) The ability of the village government to carry out the functions of strengthening village institutions is still not optimal. The main obstacle is the lack of maximum network development among fellow Maipe Village Institutions such as the PKK (Pembinaan Kesejahteraan Keluarga), KARTAR (Karang Taruna) and Community Empowerment Institutions (LPMD), adat institutions and other community institutions. The conclusion of this study is that the Maipei village government in implementing village governance after the implementation of the Village Law in 2015 showed that the village government was consistent and responsive to the Village Law. The village government draws up the RPJMDes and RKPDes according to the mechanism stipulated in the Village Law, although the new RPJMDes and RKPDes are compiled in 2017 the Maipe Village Government continues to carry out village development planning well in accordance with the mandate of the Village Law. The village financial management in the village is experiencing problems because of lack of human resources. The fact that village institutions exist in Maipe Village is still not well organized and recorded.